Princes at war ebook The bitter battle inside britain's royal family in the darkest days of wwii. - Cadbury, Deborah (2015)
In 1936, the British monarchy faced the greatest threats to its survival in the modern era — the crisis of abdication and the menace of Nazism. The fate of the country rested in the hands of George V's sorely unequipped sons: a stammering King George VI, terrified that the world might discover he was unfit to rule a dull-witted Prince Henry, who wanted only a quiet life in the army the too-glamorous Prince George, the Duke of Kent — a reformed hedonist who found new purpose in the RAF and would become the first royal to die in a mysterious plane crash the Duke of Windsor, formerly King Edward VIII, deemed a Nazi-sympathizer and traitor to his own country — a man who had given it all up for love Princes at War is a riveting portrait of these four very different men miscast by fate, one of whom had to save the monarchy at a moment when kings and princes from across Europe were washing up on England's shores as the old order was overturned. Scandal and conspiracy swirled around the palace and its courtiers, among them dangerous cousins from across Europe's royal families, gold-digging American socialite Wallis Simpson, and the King's Lord Steward, upon whose estate Hitler's deputy Rudolf Hess parachuted (seemingly by coincidence) as London burned under the Luftwaffe's tireless raids. Deborah Cadbury draws on new research, personal accounts from the royal archives, and other never-before-revealed sources to create a dazzling sequel to The King's Speech and tell the true and thrilling drama of Great Britain at war and of a staggering transformation for its monarchy.